Perinodular hydropic degeneration in uterine leiomyoma causing rapid enlargement and mimicking a myxoid smooth muscle tumor: Case report of a diagnostic challenge - Ali Al Khader; Esra Nsour; Abd-Naser Abdallat (Elsevier, 2019)
Introduction: Hydropic degeneration, sometimes reported as perinodular hydropic degeneration, is one of the various degenerative changes that can be observed in uterine leiomyomas. It can be a clinical and a histopathological diagnostic pitfall. Case Report: Here we present the case of a 40-year-old woman with leiomyoma uteri with perinodular hydropic degeneration. The tumor almost doubled in size over 2 months. Histopathological examination revealed fascicles, cords and nodules of smooth muscle cells separated by excessive amounts of extracellular material. No necrosis or significant atypia was noticed. Average mitotic activity was very low. A myxoid smooth muscle tumor could be excluded only by alcian blue special stain. The presence of floating vessels in the edematous fluid as well as hyalinization inside the tumor nodules were among the reassuring features supporting the diagnosis. Conclusion: The pathologist must be aware of this benign entity to avoid overdiagnosis, especially in the view of the alarming histology and the rapid growth. Negative findings with alcian blue special stain help establish the diagnosis. Keywords: Degeneration, Leiomyoma, Myxoid